2016
DOI: 10.1371/journal.pone.0160767
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Levels of Oxytocin in ‘Treatment Resistant Depression in Adolescents (TRDIA)’ Group

Abstract: Objective‘Treatment-resistant depression’ is depression that does not respond to an adequate regimen of evidence-based treatment. Treatment-resistant depression frequently becomes chronic. Children with treatment-resistant depression might also develop bipolar disorder (BD). The objective of this study was to determine whether serum levels of oxytocin (OXT) in treatment-resistant depression in adolescents (TRDIA) differ from non-treatment-resistant depression in adolescents (non-TRDIA) or controls. We also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
(23 reference statements)
3
11
0
Order By: Relevance
“…The association between oxytocin and prosocial behavior has not been measured during adolescence, although one study shows that adolescent males with higher salivary oxytocin levels report fewer conduct problems [82], which can be cautiously interpreted as more prosocial behavior. Finally, one study reported elevated oxytocin levels in adolescents with treatment-resistant MDD, compared to non-treatment resistant and healthy control adolescents [83•]. However, the association between prosocial behavior and oxytocin in pubertal patients with MDD remains to be studied.…”
Section: Oxytocin and Testosteronementioning
confidence: 99%
“…The association between oxytocin and prosocial behavior has not been measured during adolescence, although one study shows that adolescent males with higher salivary oxytocin levels report fewer conduct problems [82], which can be cautiously interpreted as more prosocial behavior. Finally, one study reported elevated oxytocin levels in adolescents with treatment-resistant MDD, compared to non-treatment resistant and healthy control adolescents [83•]. However, the association between prosocial behavior and oxytocin in pubertal patients with MDD remains to be studied.…”
Section: Oxytocin and Testosteronementioning
confidence: 99%
“…In previous reports, the serum OXT levels in women with post-traumatic stress disorder (PTSD) associated with a traffic accident, PTSD associated with other events, and women with schizopherenia were reported to be 69.5±32.7 pg/mL ( 23 ), 101.59±55.89 pg/mL ( 24 ), and 100±35 pg/mL ( 25 ), respectively. Attention deficit hyperactivity disorder (ADHD) ( 26 , 27 ) and autism spectrum disorder (ASD) ( 28 , 29 ) in children as well as treatment-resistant depression in adolescents ( 30 ) are reported to be associated with OXT levels. Depression was only reported to be associated with OXT levels based on the RIA method ( 5 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors specified that oxytocin production is decreased in children with callous and unemotional traits. Sasaki et al did not find any associations between oxytocin concentration in saliva and the expressiveness of depression symptoms in adolescents, though patients with treatment-resistant depression showed higher levels of oxytocin than the control cohort with non-resistant depression [45]. The oxytocin plasma level was decreased in children with attention deficit/hyperactivity syndrome, and it was negatively correlated to impulsivity and inattentiveness [46,47].…”
Section: Pathogenesis Of Internet Addiction In Terms Of Neurobiologymentioning
confidence: 99%